Structural, thermal, and morphological characteristics of cassava amylodextrins - Costa, Mariana Souza [UNESP]; Volanti, Diogo Paschoalini [UNESP]; Grossmann, Maria Victória Eiras; Franco, Célia Maria Landi [UNESP] (Wiley, 2018)
BACKGROUND: Amylodextrins from cassava starch were obtained by acid hydrolysis, and their structural, thermal and morphological characteristics were evaluated and compared to those from potato and corn amylodextrins. RESULTS: Cassava starch was the most susceptible to hydrolysis due to imperfections in its crystalline structure. The crystalline patterns of amylodextrins remained unchanged, and crystallinity and peak temperature increased with hydrolysis time, whereas thermal degradation temperature decreased, independent of treatment time and starch source. Cassava amylodextrins had similar structural and morphological characteristics to those from corn amylodextrins due to their A-type crystalline arrangements. A-amylodextrins were structurally and thermally more stable than potato amylodextrins (B-type). Starch nanocrystals (SNC) were observed by transmission electron microscopy from the third day of hydrolysis in cassava amylodextrins, whereas potato and corn amylodextrins displayed SNC only on the fifth day. A-SNC displayed platelet shapes, whereas B-SNC were rounded. The SNC shape was related to the packing form and geometry of unit cells of allomorphs A and B. CONCLUSION: Microstructures (agglomerated crystalline particles) and nanostructures (double helix organization) were observed for amylodextrins. Cassava starch was shown to be a promising material for SNC production, since it requires less hydrolysis time to obtaining more stable crystals. © 2017 Society of Chemical Industry.
Keywords: acid hydrolysis; crystallinity; nanostructure; starch; thermal properties